Mobilizing IDEAS in the Scottish Referendum: Predicting voting intention and well‐being with the Identity‐Deprivation‐Efficacy‐Action‐Subjective well‐being model. (19th November 2019) - Abrams, Dominic; Travaglino, Giovanni A.; Grant, Peter R.; Templeton, Anne; Bennett, Mark; Lalot, Fanny
Abstract : In the month approaching the 2014 Scottish Independence referendum, we tested the Identity‐Deprivation‐Efficacy‐Action‐Subjective Well‐Being model using an electorally representative survey of Scottish adults ( N = 1, 156) to predict voting for independence and subjective well‐being. Based on social identity theory, we hypothesized for voting intention that the effects of collective relative deprivation, group identification, and collective efficacy, but not personal relative deprivation (PRD), should be fully mediated by social change ideology. Well‐being was predicted to be associated with PRD (negatively) and group identification (positively and, indirectly, negatively). Unaffected by demographic variables and differences in political interest, nested structural equation model tests supported the model, accounting for 82% of the variance in voting intention and 31% of the variance in subjective well‐being. However, effects involving efficacy depended on its temporal framing. We consider different ways that social identification can simultaneously enhance and diminish well‐being and we discuss ramifications of the model for collective mobilization and separatist nationalism. Findings also suggest new directions for research on social identity, collective efficacy, and collective action.